Method for preparing lanthanum-doped cobalt-tetroxide catalyst by solid-phase co-milling and application thereof
Patent Information
- Application Number
- CN202610912797.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-06-24
AI Technical Summary
目前采用纯固相研磨法制备用于低浓度甲烷催化氧化的Co3O4催化剂,相关系统研究仍较少
(1)以六水硝酸钴、无水草酸与六水硝酸镧为原料进行纯固相研磨反应,在行星球磨机中通过机械化学法直接进行固相研磨反应。全过程不引入任何液体溶剂,避免了传统湿法合成中废液的产生与后处理问题,符合绿色化学原则。合成步骤操作流程简洁,条件易于控制,该工艺非常适合规模化放大和连续化生产,具备良好的工业转化潜力。
Smart Images

Figure CN122424826B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of low-temperature catalytic combustion technology for methane, and particularly to a solid-phase co-grinding preparation method and application of a lanthanum-doped cobalt tetroxide catalyst. Background Technology
[0002] Currently, coal mine exhaust gas is mainly emitted as part of emissions, which not only wastes resources but also exacerbates the greenhouse effect. Methane is the main component of methane gas, and achieving low-temperature catalytic oxidation of methane using highly efficient catalysts is one of the important technological approaches for managing exhaust gas.
[0003] Traditional high-activity methane oxidation catalysts mostly employ precious metals. While these catalysts exhibit high activity, they suffer from drawbacks such as high cost, limited resources, insufficient resistance to poisoning, and inadequate thermal stability, making them unsuitable for large-scale industrial applications. In contrast, transition metal oxides, especially cobalt tetroxide (Co3O4), offer advantages due to their low cost and abundant Co content. 2+ / Co 3+ With its variable valence state, strong oxygen migration ability, and high thermal stability, it is considered a promising non-precious metal methane catalyst.
[0004] Currently, Co3O4 is commonly prepared via wet chemical routes such as co-precipitation, hydrothermal methods, and sol-gel methods. These methods generally suffer from complex processes, large solvent consumption, and cumbersome post-processing steps, hindering green and large-scale production. Furthermore, due to limitations in mass transfer processes and solvent environments, there is still room for improvement in the control of crystal form, specific surface area, and dispersion of active sites in some wet-prepared Co3O4.
[0005] Solid-phase grinding is a mechanochemical method that uses external mechanical energy to promote the mixing, contact, and reaction between solid reactants. It can achieve solid-phase organic-inorganic reactions with minimal or no solvent, offering advantages such as simple process, environmental friendliness, and ease of scale-up. Currently, there is limited systematic research on the preparation of Co3O4 catalysts for the catalytic oxidation of low-concentration methane using pure solid-phase grinding. Therefore, there is an urgent need to develop a novel preparation method for Co3O4 that is simple, solvent-free, easily scaled up, and yields highly active Co3O4. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a solid-phase co-grinding preparation method for lanthanum-doped cobalt tetroxide catalysts and its application. The technical solution of this invention is as follows: In a first aspect, a solid-phase co-grinding method is provided for preparing a lanthanum-doped cobalt tetroxide catalyst, comprising: S11, weigh lanthanum nitrate hexahydrate and cobalt nitrate hexahydrate according to the molar ratio of La:Co of 0.005-0.2:1, and weigh anhydrous oxalic acid according to the molar ratio of anhydrous oxalic acid to total metal of 1-2:1. Add cobalt nitrate hexahydrate, anhydrous oxalic acid and lanthanum nitrate hexahydrate together into the ball mill jar of the planetary ball mill. S12, add grinding media to the ball mill jar for solid-phase grinding. During the grinding process, cobalt nitrate hexahydrate and lanthanum nitrate hexahydrate react with anhydrous oxalic acid in a solid-phase reaction to generate a cobalt oxalate / lanthanum oxalate composite precursor in situ. This allows La to be highly dispersed in the composite precursor and to fully contact the Co species, thus obtaining a solid-phase precursor. S13, the solid precursor obtained by ball milling is centrifuged and washed to remove unreacted impurities and raw materials, and then dried to obtain a La-containing cobalt oxalate precursor; S14, the La-containing cobalt oxalate precursor is transferred to a muffle furnace and calcined in air atmosphere to obtain a La-doped Co3O4 catalyst.
[0007] Preferably, S12 includes: Add grinding media to the ball mill jar, with a ball-to-material ratio of 3-10:1, and perform solid-phase grinding at a ball mill speed of 400-800 r / min for 1-2 hours.
[0008] Preferably, S13 is dried at a temperature of 60-80°C for 6-12 hours.
[0009] Preferably, when S14 is calcined, the calcination temperature is 300-400℃, the holding time is 2-4h, and the temperature is increased at a rate of 2-5℃ / min.
[0010] Preferably, the grinding media is zirconia balls.
[0011] In a second aspect, an application of a lanthanum-doped cobalt tetroxide catalyst is provided, wherein the lanthanum-doped cobalt tetroxide catalyst is prepared by the preparation method described in the first aspect, and the lanthanum-doped cobalt tetroxide catalyst is applied to the low-temperature catalytic combustion reaction of methane.
[0012] Preferably, when the lanthanum-doped cobalt tetroxide catalyst is applied to the low-temperature catalytic combustion reaction of methane, the low-temperature catalytic combustion reaction of methane is carried out in an atmospheric pressure fixed-bed reactor; the reaction gas composition is 0.1-1 vol% CH4, 25 vol% O2, with N2 as the equilibrium gas, and the gas space velocity is [missing value]. The loading amount of lanthanum-doped cobalt tetroxide catalyst was 0.05-0.1 g. The activity of lanthanum-doped cobalt tetroxide catalyst was evaluated by temperature-programmed catalytic methane oxidation reaction, and the low-temperature activity of lanthanum-doped cobalt tetroxide catalyst was evaluated at the temperatures corresponding to 50% and 90% methane conversion.
[0013] All of the above-mentioned optional technical solutions can be combined arbitrarily, and the present invention will not provide a detailed description of the structure after each combination.
[0014] By means of the above solution, the beneficial effects of the present invention are as follows: (1) A pure solid-phase grinding reaction is carried out using cobalt nitrate hexahydrate, anhydrous oxalic acid, and lanthanum nitrate hexahydrate as raw materials. The solid-phase grinding reaction is carried out directly in a planetary ball mill via a mechanochemical method. No liquid solvent is introduced throughout the process, avoiding the generation and post-treatment problems of waste liquid in traditional wet synthesis, which conforms to the principles of green chemistry. The synthesis steps are simple and the conditions are easy to control. This process is very suitable for large-scale scale-up and continuous production and has good industrial conversion potential.
[0015] (2) The introduction of La can form La-O-Co interactions on the Co3O4 surface and induce defect structures, thereby changing the electronic structure of Co species and Co. 2+ / Co 3+ The ratio promotes the generation of oxygen vacancies and surface active oxygen, enhances the redox cycle and lattice oxygen migration at low temperatures; at the same time, the dispersed La species can anchor Co3O4, inhibit high-temperature sintering and active phase agglomeration, thereby improving the thermal stability and deactivation resistance of the catalyst.
[0016] (3) Solid-phase grinding enables Co and La to fully contact and disperse uniformly at the microscale. After optimized calcination, a La-doped Co3O4 catalyst with complete crystal structure, small particle size and uniform dispersion can be obtained. It has a high specific surface area and strong oxygen migration ability, thus providing sufficient active sites and migratable oxygen in the low temperature region.
[0017] (4) In the low-temperature catalytic combustion reaction of methane, the La-doped Co3O4 catalyst exhibits a lower ignition temperature and a higher methane conversion rate, which helps to reduce reaction energy consumption. The La-doped Co3O4 catalyst has good thermal stability and resistance to sintering and deactivation, and can maintain its activity under long-term reaction or high-temperature conditions, thus extending its service life.
[0018] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0019] Figure 1 The images show the XRD diffraction patterns of the cobalt tetroxide catalysts prepared in Examples 1 to 3 and the comparative examples of this invention.
[0020] Figure 2 This is a schematic diagram of the temperature-conversion rate relationship curve of the methane catalytic conversion process in an embodiment of the present invention. Detailed Implementation
[0021] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and are not intended to limit the scope of the invention.
[0022] The solid-phase co-grinding preparation method for lanthanum-doped cobalt tetroxide catalyst provided in this invention uses cobalt nitrate hexahydrate (Co(NO3)2·6H2O), anhydrous oxalic acid (H2C2O4), and lanthanum nitrate hexahydrate (Co(NO3)3·6H2O) as raw materials. A simple, economical, and environmentally friendly grinding method is used to prepare a La-doped Co3O4 catalyst with good crystal structure, uniform particle size, and high specific surface area at room temperature. The specific preparation steps include: S11, weigh lanthanum nitrate hexahydrate and cobalt nitrate hexahydrate according to a La:Co molar ratio of 0.005-0.2:1, and weigh anhydrous oxalic acid according to a molar ratio of anhydrous oxalic acid to total metal of 1-2:1. Add cobalt nitrate hexahydrate, anhydrous oxalic acid and lanthanum nitrate hexahydrate together into the grinding jar of the planetary ball mill.
[0023] It should be noted that no solvent is added in step S11.
[0024] S12, grinding media are added to the ball mill jar for solid-phase grinding. During the grinding process, cobalt nitrate hexahydrate and lanthanum nitrate hexahydrate undergo a solid-phase reaction with anhydrous oxalic acid to generate a cobalt oxalate / lanthanum oxalate composite precursor in situ. This allows La to be highly dispersed in the composite precursor and to fully contact the Co species, thus obtaining a solid-phase precursor.
[0025] In one specific embodiment, S12 includes: adding grinding media into a ball mill jar, with a ball-to-material ratio of 3-10:1, and performing solid-phase grinding at a ball mill speed of 400-800 r / min for 1-2 hours.
[0026] Preferably, the grinding media is zirconia balls.
[0027] S13, the solid precursor obtained by ball milling is centrifuged and washed to remove unreacted impurities and raw materials, and then dried to obtain a La-containing cobalt oxalate precursor.
[0028] Specifically, during centrifugal washing, it can be centrifuged and washed three times.
[0029] In one specific embodiment, S13 is dried at a temperature of 60-80°C for 6-12 hours.
[0030] S14, the La-containing cobalt oxalate precursor is transferred to a muffle furnace and calcined in air atmosphere to obtain a La-doped Co3O4 catalyst.
[0031] In one specific embodiment, when S14 is calcined, the calcination temperature is 300-400℃, the holding time is 2-4h, and the temperature is increased at a rate of 2-5℃ / min. This heating rate allows the decomposition and oxidation processes of the organic ligands to proceed gently, ultimately yielding a La-doped Co3O4 catalyst with good crystal structure, uniform particle size, and high specific surface area.
[0032] This invention also provides an application of a lanthanum-doped cobalt tetroxide catalyst, which is prepared using the preparation method described in the above embodiments. The lanthanum-doped cobalt tetroxide catalyst is applied to the low-temperature catalytic combustion reaction of methane.
[0033] In specific implementation, when the lanthanum-doped cobalt tetroxide catalyst is applied to the low-temperature catalytic combustion reaction of methane, the low-temperature catalytic combustion reaction of methane is carried out in an atmospheric pressure fixed-bed reactor; the composition of the reaction gas is 0.1-1 vol% CH4, 25 vol% O2, with N2 as the equilibrium gas, and the gas space velocity is [missing value]. The loading amount of lanthanum-doped cobalt tetroxide catalyst was 0.05-0.1 g. The activity of lanthanum-doped cobalt tetroxide catalyst was evaluated by temperature-programmed catalytic methane oxidation reaction, and the low-temperature activity of lanthanum-doped cobalt tetroxide catalyst was evaluated at the temperatures corresponding to 50% and 90% methane conversion.
[0034] Specifically, due to La 3+ It has a large ionic radius and strong oxygen affinity, and easily induces defects in the Co3O4 lattice and alters the Co... 2+ / Co 3+ The ratio of rare earth elements such as lanthanum (La) can improve the surface active oxygen content and lattice oxygen migration ability; La species can regulate the surface acidity and basicity and the strength of Co-O bonds, which is beneficial to the initial activation of methane CH bonds and the redox cycle process; therefore, the introduction of rare earth elements such as lanthanum (La) into Co3O4 catalyst can significantly improve the catalytic oxidation performance of methane, thereby reducing the ignition temperature and improving the methane conversion efficiency.
[0035] In summary, the solid-phase co-grinding preparation method for lanthanum-doped cobalt tetroxide catalyst provided in this invention has the advantages of simple process, green and environmentally friendly, and scalable. It solves the problems of large solvent consumption and complex process in traditional wet route. Furthermore, by introducing La doping, it enhances the oxygen migration ability, low-temperature activity and stability of Co3O4, achieving excellent catalytic activity and stability in the low-temperature catalytic combustion reaction of methane.
[0036] To verify the beneficial effects of the preparation method provided in the embodiments of the present invention, three specific embodiments and comparative examples are provided below: Example 1
[0037] The preparation method of the lanthanum-doped cobalt tetroxide catalyst provided in this embodiment of the invention includes the following steps: According to a La:Co molar ratio of 0.01:1 and an anhydrous oxalic acid:total metal molar ratio of 1:1, 17.46 g of cobalt nitrate hexahydrate, 5.456 g of anhydrous oxalic acid, and 0.260 g of lanthanum nitrate hexahydrate were weighed and added to the ball mill jar of a planetary ball mill. Zirconia balls were added as the grinding medium, and the ball-to-material ratio was 5:1. The mixture was ground at 600 r / min in both forward and reverse directions for 2 h. The resulting solid precursor was centrifuged and washed three times with deionized water to remove unreacted impurities and raw materials. It was then dried in a 60℃ oven for 12 h to obtain a La-containing cobalt oxalate precursor. The La-containing cobalt oxalate precursor was placed in a muffle furnace and heated to 300℃ at a heating rate of 5℃ / min in air atmosphere, held at that temperature for 3 h, and then naturally cooled to room temperature to obtain a La-doped Co3O4 catalyst.
[0038] The obtained La-doped Co3O4 catalyst was used for the low-temperature catalytic combustion of methane in a fixed-bed reactor at atmospheric pressure. The activity of the La-doped Co3O4 catalyst was evaluated using a temperature-programmed methane oxidation reaction. 0.1 g of La-doped Co3O4 catalyst was weighed and thoroughly mixed with 1 g of quartz sand, then loaded into a quartz tube. Quartz wool was filled at both ends of the catalyst bed to fix the catalyst. The quartz tube was then installed in the fixed-bed reactor. The reaction gas composition was 0.1 vol% CH4, 25 vol% O2, and N2 as the equilibrium gas, with a gas hourly space velocity (GHSV) of 120,000 mL·g. -1 ·h -1 The reaction temperature was increased from 200℃ to 550℃ at a rate of 5℃ / min using a programmed temperature ramp method. The catalytic performance was evaluated by calculating the methane conversion rate using gas chromatography. The temperatures (T0) corresponding to 50% and 90% methane conversion rates were used as the benchmarks. 50 With T 90 (T0) is used as a key indicator for evaluating the low-temperature activity of catalysts. The results show that under these conditions, the T0 of the La-doped Co3O4 catalyst... 50 The temperature is 315℃, T 90 For example, 400℃ Figure 2 As shown in Table 1. Example 2
[0039] The preparation method of the lanthanum-doped cobalt tetroxide catalyst provided in this embodiment of the invention includes the following steps: According to a La:Co molar ratio of 0.03:1 and anhydrous oxalic acid:total metal molar ratio of 1:1, 17.46 g of cobalt nitrate hexahydrate, 5.564 g of anhydrous oxalic acid, and 0.779 g of lanthanum nitrate hexahydrate were weighed and added to the ball mill jar of a planetary ball mill. Zirconia balls were added as the grinding medium, and the ball-to-material ratio was 5:1. The mixture was ground at 600 r / min in both forward and reverse directions for 2 h. The resulting solid precursor was centrifuged and washed three times with deionized water to remove unreacted impurities and raw materials. It was then dried in a 60℃ oven for 12 h to obtain a La-containing cobalt oxalate precursor. The La-containing cobalt oxalate precursor was placed in a muffle furnace and heated to 300℃ in air at a heating rate of 5℃ / min, held at that temperature for 3 h, and then naturally cooled to room temperature to obtain a La-doped Co3O4 catalyst.
[0040] The obtained La-doped Co3O4 catalyst was used for the low-temperature catalytic combustion of methane in a fixed-bed reactor at atmospheric pressure. The activity of the La-doped Co3O4 catalyst was evaluated using a temperature-programmed methane oxidation reaction. 0.1 g of La-doped Co3O4 catalyst was weighed and thoroughly mixed with 1 g of quartz sand, then loaded into a quartz tube. Quartz wool was filled at both ends of the catalyst bed to fix the catalyst. The quartz tube was then installed in the fixed-bed reactor. The reaction gas composition was 0.1 vol% CH4, 25 vol% O2, and N2 as the equilibrium gas, with a gas hourly space velocity (GHSV) of 120,000 mL·g. -1 ·h -1 The reaction temperature was increased from 200℃ to 550℃ at a rate of 5℃ / min using a programmed temperature ramp method. The catalytic performance was evaluated by calculating the methane conversion rate using gas chromatography. The temperatures (T0) corresponding to 50% and 90% methane conversion rates were used as the benchmarks. 50 With T 90 (T0) is used as a key indicator for evaluating the low-temperature activity of catalysts. The results show that under these conditions, the T0 of the La-doped Co3O4 catalyst... 50 The temperature is 288℃, T 90 It is 372℃, such as Figure 2 As shown in Table 1.
[0041] Example 3: The preparation method of the lanthanum-doped cobalt tetroxide catalyst provided in this embodiment of the invention includes the following steps: According to a La:Co molar ratio of 0.05:1 and anhydrous oxalic acid:total metal molar ratio of 1:1, 17.46 g of cobalt nitrate hexahydrate, 5.672 g of anhydrous oxalic acid, and 1.299 g of lanthanum nitrate hexahydrate were weighed and added to the ball mill jar of a planetary ball mill. Zirconia balls were added as the grinding medium, and the ball-to-material ratio was 5:1. The mixture was ground at 600 r / min in both forward and reverse directions for 2 h. The resulting solid precursor was centrifuged and washed three times with deionized water to remove unreacted impurities and raw materials. It was then dried in a 60℃ oven for 12 h to obtain a La-containing cobalt oxalate precursor. The La-containing cobalt oxalate precursor was placed in a muffle furnace and heated to 300℃ in air at a heating rate of 5℃ / min, held for 3 h, and then naturally cooled to room temperature to obtain a La-doped Co3O4 catalyst.
[0042] The obtained La-doped Co3O4 catalyst was used for the low-temperature catalytic combustion of methane in a fixed-bed reactor at atmospheric pressure. The activity of the La-doped Co3O4 catalyst was evaluated using a temperature-programmed methane oxidation reaction. 0.1 g of La-doped Co3O4 catalyst was weighed and thoroughly mixed with 1 g of quartz sand, then loaded into a quartz tube. Quartz wool was filled at both ends of the catalyst bed to fix the catalyst. The quartz tube was then installed in the fixed-bed reactor. The reaction gas composition was 0.1 vol% CH4, 25 vol% O2, and N2 as the equilibrium gas, with a gas hourly space velocity (GHSV) of 120,000 mL·g. -1 ·h -1 The reaction temperature was increased from 150℃ to 550℃ at a rate of 5℃ / min using a programmed temperature ramp method. The catalytic performance was evaluated by calculating the methane conversion rate using gas chromatography. The temperatures (T0) corresponding to 50% and 90% methane conversion rates were used as the benchmarks. 50 With T 90 (T0) is used as a key indicator for evaluating the low-temperature activity of catalysts. The results show that under these conditions, the T0 of the La-doped Co3O4 catalyst... 50 The temperature was 311℃, T 90 It is 389℃, such as Figure 2 As shown in Table 1.
[0043] Comparative Example 1: 17.46 g of cobalt nitrate hexahydrate and 5.4 g of anhydrous oxalic acid were weighed and added to the grinding jar of a planetary ball mill. Zirconia balls were added as the grinding medium, with a ball-to-material ratio of 5:1. The mixture was ground at 600 r / min in both forward and reverse directions for 2 h. The resulting solid precursor was centrifuged and washed three times with deionized water to remove unreacted impurities and raw materials. The mixture was then dried in a 60℃ oven for 12 h to obtain a dry powder. The dried powder was placed in a muffle furnace and heated to 300℃ in air at a heating rate of 5℃ / min, held at that temperature for 3 h, and then naturally cooled to room temperature to obtain the Co3O4 catalyst.
[0044] The obtained Co3O4 catalyst was used for the low-temperature catalytic combustion of methane in a fixed-bed reactor at atmospheric pressure. The activity of the Co3O4 catalyst was evaluated using a temperature-programmed methane oxidation reaction. 0.1 g of Co3O4 catalyst was weighed and thoroughly mixed with 1 g of quartz sand, then loaded into a quartz tube. Quartz wool was filled at both ends of the catalyst bed to fix the catalyst. The quartz tube was then installed in the fixed-bed reactor. The reaction gas composition was 0.1 vol% CH4, 25 vol% O2, and N2 as the equilibrium gas, with a gas hourly space velocity (GHSV) of 120,000 mL·g. -1 ·h -1 The reaction temperature was increased from 200℃ to 550℃ at a rate of 5℃ / min using a programmed temperature ramp method. The catalytic performance was evaluated by calculating the methane conversion rate using gas chromatography. The temperatures (T0) corresponding to 50% and 90% methane conversion rates were used as the benchmarks. 50 With T 90 (T0) is used as a key indicator for evaluating the low-temperature activity of catalysts. The results show that under these conditions, the T0 of the Co3O4 catalyst... 50 The temperature was 338℃, T 90 It is 408℃, such as Figure 2 As shown in Table 1.
[0045] Table 1. Schematic diagram of test results for the embodiment Example 1 315 400 Example 2 288 372 Example 3 311 389 Comparative Example 1 338 408 like Figure 1 The image shows the XRD diffraction patterns of the cobalt tetroxide catalysts prepared in Examples 1 to 3 and Comparative Example 1 of this invention. Figure 1 It can be seen that both the Co3O4 catalyst and the La-doped Co3O4 catalyst samples retained the characteristic diffraction peaks of the spinel phase Co3O4, indicating that La doping did not destroy the main crystal structure of Co3O4. Compared with undoped Co3O4, the characteristic diffraction peaks of the La-doped samples showed a slight shift, indicating that the introduction of La changed the local lattice environment of Co3O4 and induced lattice distortion. Simultaneously, the diffraction peak intensity of the doped samples decreased, while the full width at half maximum (FWHM) increased, indicating a decrease in catalyst crystallinity, a reduction in grain size, and the accompanying stronger lattice microstrain and defect structure formation. The activity results from Examples 1-3 and Comparative Example 1 are combined as follows... Figure 2 As shown in Table 1, the low-temperature catalytic combustion performance of methane in the Co3O4 catalyst is significantly improved after La doping. 50 The temperature was decreased from 338℃ in the undoped sample to 315℃, 288℃, and 311℃, T 90 The temperature was reduced from 408℃ to 400℃, 372℃ and 389℃, indicating that La doping can regulate the structural defects of Co3O4, promote the generation of active oxygen and the migration of lattice oxygen, thereby enhancing the low-temperature oxidation activity of methane.
[0046] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A solid-phase co-grinding method for preparing a lanthanum-doped cobalt tetroxide catalyst, characterized in that, include: S11: Lanthanum nitrate hexahydrate and cobalt nitrate hexahydrate are weighed according to a La:Co molar ratio of 0.005-0.2:1, and anhydrous oxalic acid is weighed according to an anhydrous oxalic acid to total metal molar ratio of 1-2:
1. Cobalt nitrate hexahydrate, anhydrous oxalic acid, and lanthanum nitrate hexahydrate are added together to the ball mill jar of a planetary ball mill; no liquid solvent is added to S11. S12, grinding media are added to the ball mill jar and solid-phase grinding is carried out directly by mechanochemical method. Solid-phase grinding allows Co and La to fully contact and be uniformly dispersed at the microscale. During the grinding process, cobalt nitrate hexahydrate, lanthanum nitrate hexahydrate and anhydrous oxalic acid undergo solid-phase reaction to generate a cobalt oxalate / lanthanum oxalate composite precursor in situ. La is highly dispersed in the composite precursor and fully contacted with Co species to obtain solid-phase precursor. S13, the solid precursor obtained by ball milling is centrifuged and washed to remove unreacted impurities and raw materials, and then dried to obtain a La-containing cobalt oxalate precursor; In step S14, a La-containing cobalt oxalate precursor was transferred to a muffle furnace and calcined in air at 300-400℃ to obtain a La-doped Co3O4 catalyst with complete crystal structure, uniform particle size, and uniform dispersion. The introduction of La forms La-O-Co interactions on the Co3O4 surface and induces defect structures, altering the electronic structure of the Co species and its interaction with Co. 2+ / Co 3+ The ratio promotes the generation of oxygen vacancies and surface reactive oxygen species, enhancing redox cycles and lattice oxygen migration at low temperatures; at the same time, the dispersed La species anchor Co3O4 to inhibit the aggregation of the active phase.
2. The solid-phase co-grinding preparation method of the lanthanum-doped cobalt tetroxide catalyst according to claim 1, characterized in that, S12 includes: Add grinding media to the ball mill jar, with a ball-to-material ratio of 3-10:1, and perform solid-phase grinding at a ball mill speed of 400-800 r / min for 1-2 hours.
3. The solid-phase co-grinding preparation method of the lanthanum-doped cobalt tetroxide catalyst according to claim 1, characterized in that, The S13 is dried at a temperature of 60-80℃ for 6-12 hours.
4. The solid-phase co-grinding preparation method of the lanthanum-doped cobalt tetroxide catalyst according to claim 1, characterized in that, When S14 is calcined, the holding time is 2-4 hours, and the temperature is increased at a rate of 2-5℃ / min.
5. The solid-phase co-grinding preparation method of the lanthanum-doped cobalt tetroxide catalyst according to claim 2, characterized in that, The grinding media is zirconia balls.
6. The application of a lanthanum-doped cobalt tetroxide catalyst, characterized in that, The lanthanum-doped cobalt tetroxide catalyst is prepared by the preparation method described in any one of claims 1 to 5, and the lanthanum-doped cobalt tetroxide catalyst is applied to the low-temperature catalytic combustion reaction of methane.
7. The application of the lanthanum-doped cobalt tetroxide catalyst according to claim 6, characterized in that, When the lanthanum-doped cobalt tetroxide catalyst is applied to the low-temperature catalytic combustion reaction of methane, the low-temperature catalytic combustion reaction of methane is carried out in a fixed-bed reactor at atmospheric pressure; the composition of the reaction gas is 0.1-1 vol% CH4, 25 vol% O2, with N2 as the equilibrium gas, and the gas space velocity is 30,000-120,000 mL·g. -1 ·h -1 The loading amount of lanthanum-doped cobalt tetroxide catalyst was 0.05-0.1 g. The activity of lanthanum-doped cobalt tetroxide catalyst was evaluated by temperature-programmed catalytic methane oxidation reaction, and the low-temperature activity of lanthanum-doped cobalt tetroxide catalyst was evaluated at the temperatures corresponding to 50% and 90% methane conversion.
Citation Information
Patent Citations
Method for improving sintering resistance of cobalt oxide catalyst by lanthanum doping
CN115069259A